Prevalence of overweight among Dutch primary school children living in JOGG and non-JOGG areas - Kobes, Annita; Kretschmer, Tina; Timmerman, Margaretha C. (PLoS ONE, 2021)
Background One of the most influential integrated approaches towards reducing childhood obesity is EPODE, a program that has been translated to over 20 different countries worldwide. Aim The goal of this study was to explore how JOGG–the Dutch EPODE adaptation–might reduce overweight prevalence among children. Methods To compare whether overweight prevalence was different in JOGG areas vs. non-JOGG areas, in long-term JOGG areas vs. short-term JOGG areas, and in low SES JOGG areas vs. middle/high SES JOGG areas, secondary anthropometric and personal data of 209,565 Dutch children were mapped onto publicly available JOGG data. Results Findings showed that overweight prevalence decreased from 25.17% to 16.08% in JOGG-areas, and from 32.31% to 18.43% in long-term JOGG areas. However, when taking into account SES, the decrease in prevalence was mainly visible in low SES long-term JOGG areas. Conclusion JOGG appeared to be successful in targeting areas where overweight was most prevalent. Low SES areas that had implemented JOGG for a longer period of time, i.e., six years, appeared to be successful in decreasing overweight prevalence.
CRIS-Team Scopus Importer:2025-03-19